Detection of rotavirus in experimentally infected calves using immunoperoxidase technique - Chauhan, R S; Singh, N P (The Indian Journal of Animal Sciences, 2012)
Immunoperoxidase technique was used for the detection of rota virus antigen in the tissue sections of the intestines of experimentally infected calves. The rotavirus antigen was detected in villous epithelial cells up to day 6 post infection; and thereafter the tissue sections were negative for rotavirus antigen. The rotavirus antigen containing cells were more prominent at the tips of villi. In some cases the rotavirus antigen was demonstrated in epithelial cells of the crypts. The colon and small intestine of all control calves and colon of infected calves did not reveal any rotaviral antigen in the sections. The localization of antigen in the formalin-fixed tissue sections offers confirmatory diagnosis which can be used for epidemiological investigations particularly for retrospective studies.